2022
DOI: 10.3390/d14080608
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Morphometric, Pomological, and Fruit-Quality Traits of Apricot (Prunus armeniaca) Traditional Varieties: Implications for Landrace Differentiation at Regional Scale

Abstract: Traditional crop varieties are receiving increasing attention in sustainable agriculture, conservation genetics, and plant science because they offer significant and largely unexplored diversity. The DNA profiling of landraces is being applied to numerous crops, yet a detailed knowledge of morphological diversity is often needed to increase the efficiency of both the conservation and exploitation of local germplasm. In this work, morphological, pomological, and fruit-quality traits (16 qualitative and 16 quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These results accord with the earlier findings of Obeed et al [45] and Abdel-Sattar et al [8], who reported that the morphological and chemical characteristics of Indian jujube fruit vary greatly amongst the particular cultivars planted in Saudi Arabia. Morphometric features are important for cultivar characterization because they are technically simple, applicable in a variety of cultural contexts, and easily translatable into information that stakeholders can understand [16,46]. Different physical properties and geometric attributes, such as fruit length (L), fruit polar diameter (D1), fruit equatorial diameter, fruit weight stone weight, pulp weight, and fruit diameter, in Indian jujube cultivars showed substantial similarities and dissimilarities among different cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results accord with the earlier findings of Obeed et al [45] and Abdel-Sattar et al [8], who reported that the morphological and chemical characteristics of Indian jujube fruit vary greatly amongst the particular cultivars planted in Saudi Arabia. Morphometric features are important for cultivar characterization because they are technically simple, applicable in a variety of cultural contexts, and easily translatable into information that stakeholders can understand [16,46]. Different physical properties and geometric attributes, such as fruit length (L), fruit polar diameter (D1), fruit equatorial diameter, fruit weight stone weight, pulp weight, and fruit diameter, in Indian jujube cultivars showed substantial similarities and dissimilarities among different cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Different fruit morphometric properties, such as perpendicular axes, color, and texture features are frequently taken into account during Indian jujube classification and identification [8,[13][14][15]. However, some Ziziphus plants almost do not prominently display minute morphological variations due to some adaptive and/or commercially related forces, linguistic issues in folk taxonomy, or inconsistency in ethnobotanical nomenclature [16]. We therefore urgently need quick, accurate, and on-hand identification.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, also the relationship between the morphological and each of the two molecular classifications was very low and not significant. The literature on agamically propagated fruit trees reports usually low or non-significant correlations between DNA-based and morphological classifications [ 22 , 47 , 48 , 49 ]. This is typically explained by the fact that the employed marker systems sampled a different kind of mostly uncorrelated diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The most important area for apricot cultivation lies around Mount Vesuvius, in the Campania region, with a production of approximately 40%. [4]. Vesuvian apricots have superior qualitative characteristics that make them well suited for processing and as ingredients in traditional confectioneries and pastries [4].…”
Section: Introductionmentioning
confidence: 99%
“…[4]. Vesuvian apricots have superior qualitative characteristics that make them well suited for processing and as ingredients in traditional confectioneries and pastries [4]. The remaining apricot fruit production is distributed to local markets, as Vesuvian apricots become marketable later than fruit imported from other countries.…”
Section: Introductionmentioning
confidence: 99%